Effect of Muscle Energy Technique Combined with Conventional Rehabilitation Therapy on Elderly Patients with Knee Osteoarthritis - FAN Jingjing; HUANG Lihua; XU Yiming; LIU Kun; FANG Ping (康复学报)
ObjectiveTo observe the effect of muscle energy technique combined with conventional rehabilitation therapy on elderly patients with knee osteoarthritis (KOA) .MethodsA total of 84 patients with KOA in the rehabilitation medicine department of Shanghai Sixth People's Hospital from February 2021 to August 2022 were randomly divided into control group and observation group according to the random number sequence generated by SPSS 22.0 statistical software, with 42 cases in each group. During the course of treatment, two cases in the control group dropped due to the patient's voluntary request, a total of 82 cases were finally included, including 40 cases in the control group and 42 cases in the observation group. Both groups received conventional rehabilitation therapy (power bicycle and physical factor therapy), including power bicycle training for 20 min a time, and physical factor therapy such as dynamic interferential electricity and ultrashort wave therapy for 30 min a time (15 min a time for each item), once a day, five days a week, lasting for four weeks. The observation group received muscle energy technique treatment on the basis of the control group, 30 minutes a time, once a day, five days a week, lasting for four weeks. Before treatment, after treatment for four weeks and after treatment for six months, the Western Ontario and Manchester University Osteoarthritis Indexes (WOMAC) was used to evaluate the degree of joint pain, joint stiffness and activities of daily living of patients with KOA. Before treatment and after treatment for four weeks, a joint angle measuring ruler was used to evaluate the range of motion (ROM) of the knee joint; the isokinetic muscle strength test and training system was used to evaluate quadriceps femoris muscle strength [quadriceps femoris peak torque (PT), quadriceps femoris peak torque to body weight ratio (PT/BW)].Results① WOMAC score: compared with that before treatment, the WOMAC joint pain, joint stiffness, activity of daily living score and total WOMAC score of the two groups decreased significantly after treatment for four weeks and after treatment six months (P<0.05). Compared with the control group at the same time, the WOMAC joint pain, joint stiffness, activity of daily living score and total WOMAC score in the observation group were significantly lower after treatment for four weeks and after treatment six months (P<0.05). ② ROM, PT and PT/BW: Compared with that before treatment, ROM, PT and PT/BW of both groups were significantly higher after treatment for four weeks (P<0.05). Compared with the control group, ROM, PT and PT/BW in the observation group were significantly higher after treatment for four weeks, the difference was statistically significant (P<0.05).ConclusionMuscle energy technique combined with conventional rehabilitation therapy can effectively relieve the pain and stiffness of knee joint of patients with KOA, and improve the range of motion of knee joint and quadriceps muscle strength, which is worthy of clinical application.